Hubungan Pengetahuan dan Sikap Ibu tentang Keluarga Sadar Gizi dengan Perilaku Sadar Gizi Keluarga Balita di Desa Karangsono Kecamatan Kwadungan Kabupaten Ngawi Tahun 2013 - Verena Meirike Arbella; Erna Widyastuti; Sri Rahayu (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2013)
Malnutrition has been long concern by government. In 1998 Health Ministry launched Kadarzi program to prevent and control malnutrition use community empowerment and approach. The behaviour of nutrition aware has not been well showed by low toddler who weighed at 53.4%, exclusive breastfeeding 32.94% from 80% of government's target. The purpose of research to determine the relationships of mother knowledge and attitudes about Kadarzi with family toddler behaviour of aware nutrition at the Karangsono Village Kwadungan District Ngawi regency. The research was done at Karangsono Village using quantitative correlation with cross-sectional design. Population is mothers with infants 6-24 months at Karangsono Village. Sampling technique is using saturated samples. All samples given knowledge, attitudes, behaviour of Kadarzi questionnaires. The results there is relationship of mother knowledge and attitudes about Kadarzi with family toddler behaviour of aware nutrition with p value 0.001. Characteristic of respondent most of them have aged 20-30 years is 64.1%, primary education is 68.8%, work as housewives is 65.6%, family lived in house of 4 people is 40.6%, have good knowledge is 53.1%, have supportive attitude is 71.9%, have good behavior is 56.2%, there is correlation between knowledge and attitudes about Kadarzi with behavior nutrient. It is recommended to mothers to give exclusively breastfeeding to their babies, and behave aware of nutrition and to increase knowledge of infant nutrition.